Determining Marketing Strategy to Support Customer Relationship Management with the Apriori Algorithm - Dheatri Agrema; Febri Hadi; Pradani Ayu Widya Purnama (Journal of Computer Scine and Information Technology, 2023)
Business competition has forced companies to be more selective in implementing their marketing strategies. This increasingly rapid technological development is an aspect that can be utilized in achieving ease of doing everything. The development of this technology can have a good impact on business people, Customer Relationship Management (CRM) is one of the business strategies to meet the goals of the store. To fulfill these objectives, the authors conducted an analysis of sales transaction data using assistive devices such as data mining. Data mining is part of analytical Customer Relationship Management (CRM) which is used to find patterns in data. By applying the Apriori Algorithm or Association Rule to achieve this business strategy. The Apriori algorithm is a method for finding relationship patterns between one or more items in a dataset. By using sales transaction data at the Rahmat Elektronik Store, it is possible to find out which products are in great demand by customers every time they shop at the Rahmat Elektronik Store. The results of applying the Apriori Algorithm or Association Rule use Minimum Support 5% and Minimum Confidance 50%